A CALPHAD-MD coupled method to reveal the strengthening mechanism in precipitation-strengthening Cu-Ni-Al alloy with evolving microstructures. (March 2023) - Dong, Bowen; Peng, Gaoyu; Wu, Zhenpeng; Shan, Xingrun; Guo, Chengjun; Miao, Junwei; Qu, Jianping; Luo, Wenyan; Jie, Jinchuan; Li, Tingju
Highlights: A novel method combing CALPHAD and MD is employed to explain the simultaneous improvement of strength and ductility in precipitation strengthening Cu-Ni-Al alloy. The fraction and composition of the matrix and the precipitates are calculated by CALPHAD, and used to establish a MD model close to the real alloy. The formation of dislocation tangle and the evolution of microcrack in the DP/CP mixed region of Cu-14.7ni-3.1al alloy are simulated by MD and verified by TEM. Abstract: With the aging temperature decreasing from 973 K to 773 K for the Cu-14.7Ni-3.1Al (wt.%) alloys, a simultaneous increase of the tensile strength (from 563 MPa to 729 MPa) and the ductility (from 5.4% to 13.5%) is observed due to the decreasing size of the (Ni, Cu)3 Al precipitates (L12 ) dispersed in the Cu-rich solid solution (FCC). Calculation of phase diagram (CALPHAD) is employed to calculate the composition and fraction of the phases at the best aging temperature 773 K. Molecular dynamics (MD) models of the Cu-14.7Ni-3.1Al alloys with L12 phases in a size of 3 nm to 12 nm are established to investigate the function mechanism of the precipitates. The composition and fraction of the FCC and L12 phases in the MD models are precisely established based on the above CALPHAD results. A simultaneous increase of tensile strength and ductility is also observed during the MD tensile tests with the decreasing size of precipitates, indicating that L12 phases with the size of 3 nm efficiently interrupt the expanding path of cracks and contribute to the homogeneous distribution of dislocations during deformation. It is also proven by MD that cracks firstly form and expand in the discontinuous precipitation (DP) region in which precipitates have the larger size than that in a continuous precipitation (CP) region. In this work, a CALPHAD-MD coupled method is proposed to quantitatively reveal the relationship between microstructures and mechanical properties of the precipitation-strengthening Cu-Ni-Al alloy with the specific composition and microstructure, which can be effectively extended to the design of novel precipitation-strengthening alloys.